PENGARUH METODE KOMUNIKASI EFEKTIF SBAR TERHADAP EFEKTIFITAS PELAKSANAAN TIMBANG TERIMA PASIEN DI RUANG GRIYATAMA RSUD TABANAN - Ketut Suardana (Jurnal Skala Husada : The Journal of Health, 2018)
Abstract. Communication frame work has been done at Tabanan Hospital based on konventional model without clearly topic. The problem  appear is nurses didn’t known patient problem completely. Effective  communication based SBAR when handover time has been applaid at Sanglah Hospital whenever fulfill JCI (Joint Commission Internasional) standard. Effective  communication verry important to ensure patient safety and quality services. The aim of this research is to analysis the effect of SBAR communication with efectivity of handover. Desain of this reserch is quasi eksperiment from  27`nurses at Griyatama  word Tabanan hospital with total sampling technic. Data was collected by observation process, conten and time handover on July-September 2015. Statistic test by t test with α = 0.05. Everage of time for handover in the morning shift after treatment is 5,73 minute and afternon 3,48 minute. The conclussion is the effect of SBAR communication model for effectivity of handover with  r =0,832 and t = 4,847 and p value 0,001 ( α = 0,05).  Keywords : effectivity, SBAR Communication, Handover